Tingkat Daya Tahan Jantung Paru Mahasiswa Olahraga Angkatan 2019 Selama Pandemi Covid - Dwi Handoko; Eko Bagus Fahrizqi; Rizki Yuliandra (Journal of Physical Education, 2020)
Everyone must have the ability to endure the heart and lungs of the body, especially for activities in physical activities. For sports students, the ability of heart and lung endurance is an important asset in carrying out activities, not only to support activities in lectures but also to support activities outside of lectures. This study aims to measure the level of cardiovascular endurance. Tests and measurements were carried out using the 1.2 km running test. The sample to be studied is sports education students class 2019, Indonesian technocrat University. This research is a survey analysis research using descriptive statistics. From the results of data collection, it was found that 5 students with a percentage of 6.41% had very good heart and lung levels. Students with the ability of heart-lung level who were classified into good categories were 23 students with a percentage of 29, 48%. Classification of pulmonary heart rate in the medium category was 48 students with a percentage of 62.54%. Thus, the level of cardiovascular endurance of sports education students class of 2019 is classified as moderate.